Causas de la liquidación de Cruz Blanca EPS y efectos en sus partes interesadas (2022)
The health service in Colombia is a fundamental right for all inhabitants, this can be public or private, however, it is true the strong criticism and disagreements of Colombians against this social sector, this is why the article below aims to investigate the liquidation of the EPS Cruz Blanca in Colombia. For the development of this research, the three causes of the liquidation were identified: the financial situation, the lack of protection of the members and the lack of guarantee in the provision of health services; in addition to highlighting the effects on the required parts of the EPS: the massive cancellation of employment contracts, the impossibility of cancelling outstanding financial obligations to both suppliers and the state, and the forced administrative intervention of assets, assets and businesses through the liquidator Felipe Negret Mosquera, and finally investigated the mechanisms used by the state against the precautionary measure in the intervention of the liquidation, according to the provisions of article 5 of decree 1424 of 2019